Influence Of Training and Work Motivation On Employee Performance at PT PTPN VII Bandar Lampung During the Covid-19 Pandemi - Nabil, Harit Alghoffar; Habiburrahman, Habiburrahman (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
The results of the initial observations that were tried, and the initial information about the gamutana, show that there are several directions that PT PTPN VII Bandar Lampung's human resources are not running optimally. Markers that show the HR performance of PTPN VII Bandar Lampung have not yet been maximized. The purpose of this research is to identify the influence of training and work motivation on the work performance of PTPN VII Bandar Lampung officers during the Covid-19 pandemic. This research procedure uses quantitative research. Data analysis using multiple linear regression analysis. Based on the results of purification and sanding, so that an example of t-test results for pesantren variables can be taken as 10,799 (count t = 10,799 t table = 1,658 t table = 1,658 variable 1,658. arithmetic = 6,140 t table = 1,658) which means there is a direct influence on the target PTPN VII Bandar Lampung. percentage of employees of PT PTPN VII Bandar Lampung.